2018
DOI: 10.3390/molecules23051137
|View full text |Cite
|
Sign up to set email alerts
|

Fingerprint-Based Machine Learning Approach to Identify Potent and Selective 5-HT2BR Ligands

Abstract: The identification of subtype-selective GPCR (G-protein coupled receptor) ligands is a challenging task. In this study, we developed a computational protocol to find compounds with 5-HT2BR versus 5-HT1BR selectivity. Our approach employs the hierarchical combination of machine learning methods, docking, and multiple scoring methods. First, we applied machine learning tools to filter a large database of druglike compounds by the new Neighbouring Substructures Fingerprint (NSFP). This two-dimensional fingerprint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…This phenomenon is also observed in the structural difference between the ergotamine-bound forms of 5HT 1B R and the 5HT 2B R; the shorter distance between TM5 and TM6 in the 5HT 2B R appear to play a role in the stronger bias of ergotamine at this receptor. Investigations into ligand selectivity for 5HT 2B R over 5HT 1B R found that selectivity is determined by non-conserved amino acid residues in the extracellular secondary binding pocket involving ECL2, as previously shown for other aminergic receptors [ 34 , 35 ].…”
Section: Resultssupporting
confidence: 54%
“…This phenomenon is also observed in the structural difference between the ergotamine-bound forms of 5HT 1B R and the 5HT 2B R; the shorter distance between TM5 and TM6 in the 5HT 2B R appear to play a role in the stronger bias of ergotamine at this receptor. Investigations into ligand selectivity for 5HT 2B R over 5HT 1B R found that selectivity is determined by non-conserved amino acid residues in the extracellular secondary binding pocket involving ECL2, as previously shown for other aminergic receptors [ 34 , 35 ].…”
Section: Resultssupporting
confidence: 54%
“…Among them, compound 37 (Table 3) showed high binding affinity (K i = 23 nM) and antagonist activity for the 5-HT 2B R, with 12-fold binding selectivity and 170-fold functional selectivity for the 5-HT 2B R over the 5-HT 2C R [150]. In 2018, Rataj et al combined a fingerprint-based machine learning approach and molecular docking that led to the identification of compound 38 (Table 3) [151]. Notably, compound 38 showed potent binding affinity (K i = 0.3 nM) and >10,000-fold selectivity over other five tested 5-HTRs [151].…”
Section: Chromane Derivativesmentioning
confidence: 99%
“…In 2018, Rataj et al combined a fingerprint-based machine learning approach and molecular docking that led to the identification of compound 38 (Table 3) [151]. Notably, compound 38 showed potent binding affinity (K i = 0.3 nM) and >10,000-fold selectivity over other five tested 5-HTRs [151]. In addition, in 2018, as a proof-of-concept of halogen bonding in designing 5-HT 2B R ligands, a series of halogensubstituted analogs of doxepin (K i = 25.3 nM for the 5-HT 2B R) were synthesized.…”
Section: Chromane Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…GPCRs are also the subject examined in the contribution by Bojarski, Keserü, and coworkers [ 8 ]. In this study, they report a computational protocol to find compounds with selectivity between two receptors: 5-HT 2B versus 5-HT 1B .…”
mentioning
confidence: 99%